Evaluasi Potensi Lahan Untuk Pengembangan Tanaman Jagung Di Kecamatan Muara Bangkahulu Kota Bengkulu - Susianti, Helda; Dwi Yanti, Yus; Palupi, Dora; Siahaan, Limartaida (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Corn is a strategic food crops in Indonesia besides rice and soybeans and efforts to meet their needs is through the expansion of crop land. This study aimed to obtain a map of the suitability of land for the cultivation of corn and draw up recommendations for improving the productivity of land management in Muara Bangkahulu District, Bengkulu City. The research was carried out from December 2020 to February 2021. Implementation of this study consists of four stages those are, preparation stage, the field survey, analysis and interpretation of data, and the determination of land suitability classes. The information that obtained are presented with descriptive to determine land suitability classes, as well as obtaining the land suitability class relationship with the productivity of corn in the subdistrict of Muara Bangkahulu, Bengkulu City. The results of research showed that from 2,396 ha area of Muara Bangkahulu Bengkulu city, which can be used mainly for agricultural expansion include 25.4 hectares of open land, shrubs 125.8 ha, 587.5 ha of mixed farms and rice fields 695.2 ha. For the development of corn plants can be done in the open land and shrubs with an area of 151.2 ha of potential land are suitable for the 76.87 ha and 74.33 ha of corn crops are not suitable. Recommendations to improve the management of land suitability classes actually be potentially which are aplication with dolomite and calcite.